Examining Instructional Models in Enhancing 4C Skills among Primary School Students - Melkianus Panda Huki; Markhamah Markhamah; Masduki Masduki (Al-Qalam Institue, 2026)
21st-century education must emphasize the development of the 4Cs as essential competencies for elementary school students in remote areas, such as those at elementary school. This study aims to identify and analyze the learning models used by teachers and to examine their contribution to the development of critical thinking, creativity, communication, and collaboration skills. This research method with a descriptive approach. The research subjects consisted of 3 teachers and 30 fourth- and fifth-grade students at elementary school, who were selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification, with validity ensured through source and method triangulation. The results of the study indicate that the Cooperative Learning and Problem-Based Learning models contribute positively to the development of students’ communication and collaboration skills through group discussions, teamwork, and collaborative problem-solving. However, critical thinking skills and creativity still need to be improved. In addition, challenges were identified, including limited facilities and teachers’ lack of competence in implementing 4C-based learning. The implications of this study highlight the importance of enhancing teachers’ pedagogical competence and providing equate learning resources to optimize the implementation of 4C-based learning in elementary schools.